Spain : Financial Sector Reform-Final Progress Report. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses key findings of the progress report on financial sector reforms in Spain. Spain's European Stability Mechanism (ESM)-supported program of financial sector reform aimed to assist economic recovery by promoting financial stability. The program was adopted in mid-2012. The Spanish authorities' implementation of the program has been steadfast. All of the program's specific measures are now complete. Major structural reform efforts in a variety of areas (including labor and fiscal policies) will need to continue to achieve sufficiently rapid growth to bring unemployment down to reasonable levels over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet